2001
DOI: 10.1021/ie000922a
|View full text |Cite
|
Sign up to set email alerts
|

DRIFT Studies for the Reaction and Adsorption of Alcohols and Isobutylene on Acidic Resin Catalysts and the Mechanism of ETBE and MTBE Synthesis

Abstract: Diffuse reflectance FT-IR spectra of methanol and ethanol on Amberlyst 15 and on a synthesized acidic resin catalyst indicate that alcohol molecules are adsorbed by forming hydrogen bridges with the -SO 3 H sites of the catalyst and among themselves. Some of the alcohol molecules were found to be strongly chemisorbed by dissociation of one or two hydrogen atoms. Isobutylene was also found to be strongly adsorbed by forming a bridged structure between the adsorbed alcohol molecules and the -SO 3 H groups. DRIFT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 18 publications
(48 reference statements)
1
18
0
Order By: Relevance
“…Kinetic studies reported in the literature10–15 and our recent DRIFT [diffuse reflectance FTIR (spectroscopy)] studies16 showed that a Langmuir–Hinshelwood‐type reaction mechanism, involving adsorbed alcohols and tert ‐olefins, gave good agreement with the kinetic data. However, Rideal–Eley‐type reaction mechanisms, involving fluid‐phase isoolefins and adsorbed alcohols in the rate‐determining step of the reaction, were also considered in a number of other studies 17–19.…”
Section: Introductionsupporting
confidence: 53%
See 1 more Smart Citation
“…Kinetic studies reported in the literature10–15 and our recent DRIFT [diffuse reflectance FTIR (spectroscopy)] studies16 showed that a Langmuir–Hinshelwood‐type reaction mechanism, involving adsorbed alcohols and tert ‐olefins, gave good agreement with the kinetic data. However, Rideal–Eley‐type reaction mechanisms, involving fluid‐phase isoolefins and adsorbed alcohols in the rate‐determining step of the reaction, were also considered in a number of other studies 17–19.…”
Section: Introductionsupporting
confidence: 53%
“…There are a number of mechanisms, including Langmuir–Hinshelwood and Rideal–Eley‐type rate models, proposed in the literature for such etherification reactions 9, 10, 13, 1719. From the DRIFT studies conducted in our previous work16 it was shown that adsorbed alcohols and adsorbed isoolefin molecules both participate in the reaction mechanism in vapor‐phase etherification reactions. However, the adsorption equilibrium constants of alcohols are much higher than the adsorption equilibrium constants of isoolefins.…”
Section: Resultsmentioning
confidence: 99%
“…Thus loading the active sulfonic resin on the surface of a solid carrier facilitates the increased selectivity of the catalyst. The active centers in samples of this series of catalysts are uniform in structure and are acid sulfonic groups [14] which allows for the correlation of the catalytic activity of the sulfonic resins with the total acidity of the samples.…”
Section: Resultsmentioning
confidence: 99%
“…One study reported that ethanol adsorbed from n-heptane onto a strong acid exchanger/catalyst (Amberlyst 15), with equilibrium binding constants reported to be in the range 10 1 -10 2 M -1 . 36 A second set of studies reported that phenols adsorbed from heptane and toluene onto tertiary amine sorbents via a hydrogenbonding mechanism. Binding constants for these studies were reported to be 10 0 -10 2 M -1 depending on the phenol.…”
Section: Results and Discusssionmentioning
confidence: 99%